A Synthetic Triple Helical Collagen Peptide as a New Agonist for Flow Cytometric Measurement of GPVI-Specific Platelet Activation - Sang, Yaqiu; Huskens, Dana; Wichapong, Kanin; de Laat, Bas; Nicolaes, Gerry A. F.; Roest, Mark (Thrombosis and Haemostasis, 2019)
Synthetic cross-linked collagen-related peptide (CRP-XL) is a glycoprotein VI (GPVI) receptor activator for platelet activation. This triple helical peptide, widely used in platelet function tests, is synthesized and cross-linked through cysteine residues at its N-terminus and C-terminus. Currently, there is only one laboratory, which is capable to produce this valuable peptide for clinical applications. In an attempt to provide a standardized alternative for CRP-XL, we developed a synthetic triple helical collagen peptide (STH-CP) with the same primary sequence as CRP-XL (GPC-(GPO)10-GPCG-amide)3, which was both on the C-terminus and on the N-terminus fixed on a scaffold with a binding side for each of the three peptides. The performance of STH-CP on platelet function was studied using flow cytometry and compared with CRP-XL. We found that platelet activation pattern in response to STH-CP and CRP-XL is similar, although the STH-CP requires sixfold higher concentrations to activate platelets to the same state. The intra-assay percent coefficient of variation of STH-CP and CRP-XL were both < 5% and the interindividual variation measured in 118 individuals for both peptides was around 23 and 21% for αIIbβ3 activation and P-selectin expression, respectively. The STH-CP in ready-to-use reaction mix has lower variation than CRP-XL over 1-year storage. In reference values and seasonal variation study, the platelet activation response showed a strong correlation between STH-CP and CRP-XL.Our findings show that this new STH-CP is a stable and potent platelet GPVI agonist which can induce the same reproducible platelet activation as CRP-XL and that STH-CP can be considered as a good alternative for CRP-XL.
Keywords: platelet activation; cross-linked collagen-related peptide; synthetic triple helical collagen peptide